Pentingnya Budaya dalam Bimbingan Konseling Islam bagi Remaja - Viva Justicia Foreva; Sari Dusni (STAI Hubbulwathan Duri, 2021)
Talking about teenagers is always interesting, from the point of view of biological, psychological, social and spiritual conditions. For spiritual conditions, adolescents are in a critical condition of thinking about religious activities, so they always want the effects of religious practices to get a sense of security. Therefore, what are the ways and experiences that teenagers must have in order to be able to adapt in changing situations or very diverse cultures. Adolescent adaptability is needed in order to remain independent and ready to face the future that has been planned (even the demands of the family and the environment). Guidance and counseling with a cultural approach of